A compact multiband antenna based on metamaterial for L-band, WiMax, C-band, X-band, and Ku-band applications - Youssef Frist; Mourad Elhabchi; Mohamed Nabil Srifi (Universitas Ahmad Dahlan, 2024)
A novel multiband metamaterial (MTM) unit cell antenna loaded with split ring resonator (SRR) slots that resonates at seven bands, which are (1.91 GHz), (3.6 GHz), (6.25 GHz), and (8.69 GHz, 9.69 GHz, 10.70 GHz), and 12.33 GHz of the spectrum, making it suitable for L-band, worldwide interoperability for microwave access (WiMax), C-band, X-band downlink, and Ku-band applications, respectively, is proposed and discussed in this work. The proposed antenna has a very compact size of 14×15×1.6 mm3 with an FR4 substrate. The simulation results show that the presented antenna attains a reflection coefficient of less than -10 dB (S11 -10 dB) and a radiation pattern across all operating bands. In addition, the suggested antenna provides good gains over the resonant frequency signals with an average of 6.75 db. The antenna simulations and parametric studies have been done using both computer simulation technology microwave studio (CST microwave studio) and high frequency structure simulator (HFSS) to confirm the obtained simulation results.